New Analytical Method for Quantifying Flavoring Chemicals of Potential Respiratory Health Risk Concerns in e-Cigarette Liquids - Page, Michelle K.; Goniewicz, Maciej L. (Frontiers in Chemistry, 2021)
Numerous flavoring chemicals are added to e-cigarette liquids to create various flavors. Flavorings provide sensory experience to users and increase product appeal; however, concerns have been raised about their potential inhalation toxicity. Estimating potential health risk of inhaling these chemicals has been challenging since little is known about their actual concentrations in e-cigarette products. To date, a limited number of analytical methods exist to measure the concentrations of flavoring chemicals in e-cigarette products. We have developed an analytical method that accurately and precisely measures the concentrations of 20 flavoring chemicals of potential inhalation risk concerns: 2,3,5-trimethylpyrazine, acetoin, benzaldehyde, benzyl alcohol, butanoic acid, dl-limonene, ethyl maltol, ethyl salicylate, ethyl vanillin, eucalyptol, eugenol, furaneol, isovanillin, l-menthol, maltol, methyl salicylate, pulegone, trans-cinnamaldehyde, triacetin, and vanillin. Calibration and QC solutions were prepared in 50:50 propylene glycol (PG):vegetable glycerin (VG) and 5% H2O and flavoring concentrations ranging from 0.02 to 10.00 mg/ml. Samples of commercial e-cigarette liquids, calibration and QC solutions were combined with 30 µL of an internal standard mix (benzene-d6, pyridine-d5, chlorobenzene-d5, naphthalene-d8 and acenaphthene-d10; 1 mg/ml each) and were diluted 100-fold into methanol. Analysis was performed on an Agilent 7890B/7250 GC/Q-TOF using a DB-624UI column (30 m x 0.25 mmID x 1.4 μm film thickness), with a total runtime of 13.5 min. Calibration curves were fit using a weighted quadratic model and correlations of determination (r2) values exceeded 0.990 for all chemicals. Bias and precision tests yielded values less than 20% and lower limits of quantitation (LLOQ) ranged from 0.02 to 0.63 mg/ml. Over 200 commercially available products, purchased or collected from adult e-cigarette users and spanning a range of flavor categories, were evaluated with this method. Concentrations of pulegone, a suspected carcinogen, varied from below limit of quantitation (BLOQ) to 0.32 mg/ml, while acetoin and vanillin, known precursors to more cytotoxic byproducts, ranged from BLOQ to 1.52 mg/ml and from BLOQ to 16.22 mg/ml, respectively. This method features a wide dynamic working range and allows for a rapid routine analysis of flavoring additives in commercial e-cigarette liquids.